Illocutionary acts and adversarial questioning in post-match interviews / Stippie Chee Wei How - Stippie Chee , Wei How (2018)
The advancement of journalism technology has seen the introduction of broadcast interviews, which often feature unscripted questioning and answering between journalists and interviewees. Over the years, studies of adverseness in interviews have been focusing mostly on political interviews, with other types of interview such as entertainment and sports explored limitedly. This study aims to investigate the effects of match outcome on what kind of illocutionary acts and how they are used by Jose Mourinho, as well as the adverseness used in the journalists’ questioning and how they are used against Jose Mourinho by adopting Searle’s Classification of Illocutionary Acts (1976) and Clayman’s Question Analysis System (2002) as analytical frameworks. Classification of Jose Mourinho’s utterances is based on illocutionary point, direction of fit and psychological condition identification, while adverseness in the interviewers’ questions is analysed by identifying the adverseness indicators. The representative utterances were aimed at collecting the Portuguese manager’s opinions of the match, which also explains why no declarations were used. The use of directives in defeat/draw matches were used only to avoid certain questions from having to be answered, while such directives were not needed when matches were won. The use of suggestive questions by the interviewers shows their approach to “obtain” answers when matches were won. However, questions were more hostile and persistent with their follow-up questions when matches were lost/drawn. Finally, more indirectness were found after matches were lost/drawn which shows the interviewers’ cautious approach to ask questions regarding refereeing decisions.